Armenians in Turkey after the Second World War: An Archival Reader of USSR Consular Documents by Talin Suciyan - MassisPost (MassisPost, 2025)
This reader brings to light newly discovered archival material compiled by the Soviet Consulate in Istanbul. The book reveals the lives and experience of Armenians in Turkey in the 1940s, with a particular focus on the process of emigration to Soviet Armenia. The accounts, translated for the first time into English, are comprised of Soviet officials’ reports and first-hand testimony by survivors of their lives during the post-genocide period, making this an invaluable new contribution to the existing collections of Armenian survival testimonies.